Development of Humanities Education to Increase Cultural Awareness and Critical Skills - Nurul Fadhilah (Kamara Journal, 2024)
Humanities education plays a crucial role in building cultural awareness and critical skills in society. This article explores strategies and approaches in the development of humanities education for this purpose. Through a comprehensive literature review, key concepts such as cultural understanding, critical analysis, and self-reflection are discussed to enhance cultural awareness and critical skills. The article also describes effective teaching and learning methods in the context of humanities education. The findings provide valuable insights for educators, education practitioners, and education policy to strengthen the role of humanities education in enhancing cultural awareness and critical skills in society. Thus, humanities education is not only an important foundation in cultural understanding, but also a tool to develop critical analytical skills, helping to prepare individuals to face increasingly complex global challenges.